A Comprehensive Magnetic Survey of a Neolithic Causewayed Enclosure in West‐central France for the Interpretation of Archaeological Features. Issue 1 (22nd October 2014) - Ard, Vincent; Mathé, Vivien; Lévêque, François; Camus, Adrien
Abstract This paper describes an interdisciplinary study of the Neolithic causewayed enclosure of Bellevue (Chenommet, France). Geophysical investigations and archaeological excavations were used alternately in order to optimize the acquisition of accurate data at different spatial scales: mapping of major structures was obtained by magnetic prospection of the whole site, while excavation identified small features weakly expressed in the prospecting results. Measurements of magnetic susceptibility and total magnetic field anomalies were also recorded during the excavation in order to identify the source of the magnetic signal of the ditches. This mutual transdisciplinary contribution is also methodological: the geophysics reveals archaeological information invisible to the eye of the archaeologist and, in turn, the excavation allows refinement of the interpretation of the geophysical data by identifying the sources of signal variations. This article presents the results of the first comprehensive magnetic mapping of a Neolithic causewayed enclosure in the west of France. Copyright © 2014 John Wiley & Sons, Ltd.